2017
DOI: 10.1038/s41598-017-11849-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential bias of daily soil CO2 efflux estimates due to sampling time

Abstract: Soil respiration (Rs) has been usually measured during daylight hours using manual chambers. This approach assumes that measurements made during a typical time interval (e.g., 9 to 11 am) represent the mean daily value; locally, this may not always be correct and could result in systematic bias of daily and annual Rs budgets. We propose a simple method, based on the temporal stability concept, to determine the most appropriate time of the day for manual measurements to capture a representative mean daily Rs va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Even considering that out‐of‐bag r 2 can underestimate model performance, our model fit was not as high as those reported in similar studies (Bond‐Lamberty et al, ; Wu et al, ). This could have been due to a number of reasons: a more heterogeneous landscape that is not as fully represented by sampled plot locations, higher spatial resolution of our predictions, a smaller range of variability in respiration (due to both seasonal averaging and restricting sampling to a single forest type) compared to past efforts, lack of high‐resolution climate data, or timing of soil respiration sampling (Cueva et al, ). Soil respiration is highly variable over time, both seasonally and diurnally.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even considering that out‐of‐bag r 2 can underestimate model performance, our model fit was not as high as those reported in similar studies (Bond‐Lamberty et al, ; Wu et al, ). This could have been due to a number of reasons: a more heterogeneous landscape that is not as fully represented by sampled plot locations, higher spatial resolution of our predictions, a smaller range of variability in respiration (due to both seasonal averaging and restricting sampling to a single forest type) compared to past efforts, lack of high‐resolution climate data, or timing of soil respiration sampling (Cueva et al, ). Soil respiration is highly variable over time, both seasonally and diurnally.…”
Section: Discussionmentioning
confidence: 98%
“…Mismatches between tower‐ and chamber‐based estimates of respiration are common (Bolstad et al, ; Speckman et al, ; Wang et al, ). Soil respiration sampling bias as discussed above could have contributed to this (Cueva et al, ). Another cause of mismatch could be errors in the estimated EC footprint shape and size that are not taken into account by our predicted estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Similar dynamics have been observed in other forest ecosystems when root respiration is diminished, with some time lag, following a limitation in tree transpiration (Adachi et al, ; Bekku et al, ). Ecosystems with such (possibly transient) water limitations may have quite different dynamics; for example, at a dry shrub site Cueva et al () found the optimal measurement time to be at night, with potential biases ranging from −29% to +40%.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Davidson et al () found that diel variation was ~25% of the daily mean, and that midmorning was the best time to measure a representative daily flux. This time‐of‐day question was shown to have a large effect in shrubland (Cueva et al, ) and agricultural (Parkin & Kaspar, ) ecosystems. In general it will be more important in systems with larger diel flux variability (Jian et al, ), driven by strong day‐to‐night contrasts; conversely, it might be expected to be weaker in the long summer daylight at high latitudes, for example.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements were collected across all collars on each sampling date between approximately 09:00-12:00. Previous studies have demonstrated that instantaneous soil carbon flux in the late-morning is a good approximation of the daily mean soil CO 2 flux at a northeastern U.S. temperate forest site [42], thus avoiding potential biases in the effect of measurement time on soil flux [43]. During each chamber measurement, soil temperature was measured with a digital thermometer inserted 10 cm below the soil surface adjacent to the chamber.…”
Section: Chamber Measurements and Flux Calculationsmentioning
confidence: 99%